2017
DOI: 10.21837/pmjournal.v15.i6.223
|View full text |Cite
|
Sign up to set email alerts
|

Feeder Mode Choice Selection Behavioural Modelling: The Case of KTM Komuter, Kuala Lumpur

Abstract: Transit oriented development propagates the use of feeder services such as buses, taxis and paratransit to support the main rail trunks (Taylor, 1982; Limtanakool et.al, 2006;Alshalalfah & Shalaby, 2007). This paper attempts at explaining the preferences of passengers of a Malaysian rail service towards feeder buses, factors influencing their choices and recommendations to encourage the KTM Komuter passengers to switch mode to feeder services instead of driving their private vehicles to and from stations. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…IPTs have excellently performed the feeder function's capabilities from their origin to public transportation terminals in areas not covered by public transportation modes. Bachok and Zin [12] studied the travel behaviour of rail passengers. In their study, there were described various factors to encourage passengers to use feeder services in lieu of driving their personal vehicles to and from stations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IPTs have excellently performed the feeder function's capabilities from their origin to public transportation terminals in areas not covered by public transportation modes. Bachok and Zin [12] studied the travel behaviour of rail passengers. In their study, there were described various factors to encourage passengers to use feeder services in lieu of driving their personal vehicles to and from stations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chiu Chuen, Karim, and Yusoff, (2014), in their research within Klang Valley of Malaysia, had identified https: //doi.org/10.15405/epms.2019.12.47 Corresponding Author: Zakiah Ponrahono Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 2421-826X 483 the rail-and-bus network is among the significant attraction factors that can attract mode shift toward using public transport as an alternative to make and complete their trip. Apart from that, unreliable frequency and routes, lack of provision of service, and inconsistence partnership between KTM commuter stations and service provider were among the refusal factors of passenger in feeder bus service (Bachok & Mohd Zin, 2017). This study includes identification of availability of the bus stops/signage as part of study to asses feeder bus facilities components, as we assume that these facilities contribute to users' convenience to access feeder bus service.…”
Section: Problem Statementmentioning
confidence: 99%
“…Hence, the accessibility of an existing feeder network is an important determinant in yielding ridership (Tabassum, Tanaka, Nakamura, & Ryo, 2017) as it eases access to the transport services. Globally, feeder shuttle service is the most common method used to encourage rail ridership (Anspacher, Khattak, & Yim, 2005) as it connects different modes of transportation (Bachok & Zin, 2017) and considered the supplementary role required for sustainable development of urban transit system (Hu et al, 2012), while feeder routes serve as linkage between local areas (demand) with main transit networks (Ciaffi, Cipriani, & Petrelli, 2012). In brief, integrating bus service facilities and features with urban rail transit services could bring significant benefits to the development of urban public transportation systems.…”
Section: Introductionmentioning
confidence: 99%